Thermal processing to bainite structure of cast iron details - L. R. Dudetskaja; A. I. Pokrovsky; I. S. Gaukhshtein; M. I. Demin; P. S. Gurchenko (Литьë и металлургия, 2002)
The schemes of bainite reaction for cast iron are given. The different factors having an influence on structure formation are described. The concrete modes of heat treatment of gear out of cast iron for bainite in conditions of MAZ are offered.